EFFECTIVE SUPERVISION AND SKILL DEVELOPMENT FROM UMK UNDERGRADUATE STUDENTS’ PERSPECTIVE - Seri Intan, M; Seri Bunian, M2, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
There are many factors that determine the success of final year project students in doing their undergraduate programs. The aim of this paper is to examine elements of effective supervision from the final year students’ perspective and to determine the predictor toward student skill development throughout the supervision process. Data were analyzed using SPSS. The Significant level used was 0.05. T- Test and One way ANOVA were conducted to determine the differences between supervision process based on gender and program. The multiple-regression analysis was used to analyze the relationship between the dependent variable (criterion) and several predictor variables (predictors). Results suggest that the four most important elements of supervisors are: guidance, feedback, interpersonal communication and expertise. Meanwhile Infrastructure also considered as important element in the supervision process. Regression model showed that the 69.4% contribution of the three predictor (Feedback, Expertise, Guidance) to student skills development were significant while, the predictor namely Interpersonal Communication were insignificantly correlated.